Variable range hopping-assisted parasitic channel leakage in AlN/GaN/AlGaN HEMTs on Si - Liu, Siyu (2024)
This work investigates the off-state leakage characteristics of AlN/GaN/AlGaN high electron mobility transistors (HEMTs) on Si substrate with varying mesa depths and uncovers the existence of a parasitic channel associated with the AlGaN back barrier. Significant differences in off-state leakage up to three orders of magnitude were observed between devices fabricated using different mesa depths. The electrical properties of AlN/GaN/AlGaN HEMTs were measured, and it was found that there is a N-type parasitic channel in the unintentionally doped AlGaN back-barrier. Analysis of the isolation test structure, which retains this parasitic channel, reveals a buffer leakage of 12.8 mA/mm and a sheet resistance of 7739.1 Ω/sq, as a result of the parasitic channel. The depletion electric field strength of the parasitic channel is 3.2 × 105 V/cm. Temperature-dependent I-V curves obtained from the isolation area affirm that the primary leakage mechanism is two-dimensional variable range hopping along the sidewall. As the isolation distance extends from 3 to 5 μm, the slope of the fitting line decreases from −53.14 to −126.11 due to increased resistance.